2020
DOI: 10.1039/c9bm01750j
|View full text |Cite
|
Sign up to set email alerts
|

Angiopep-2 conjugated nanoparticles loaded with doxorubicin for the treatment of primary central nervous system lymphoma

Abstract: APP nanoparticle was developed to deliver DOX for the treatment of PCNSL. The results indicated that APP@DOX could overcome the BBB, and significantly prolong the survival time of mice with an intracranial SU-DHL-2 lymphoma xenograft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…As such, a study from 2019 tried to reconciliate these features by synthesizing conjugated nanoparticles loaded with DOX for the treatment of PCNSL [130]. In their study, the authors used an approach previously reported in the literature which aimed to target lowdensity lipoprotein receptor-related protein (LRP) [131].…”
Section: Primary Central Nervous System Lymphoma (Pcnsl)-enhancing Bbb Crossingmentioning
confidence: 99%
“…As such, a study from 2019 tried to reconciliate these features by synthesizing conjugated nanoparticles loaded with DOX for the treatment of PCNSL [130]. In their study, the authors used an approach previously reported in the literature which aimed to target lowdensity lipoprotein receptor-related protein (LRP) [131].…”
Section: Primary Central Nervous System Lymphoma (Pcnsl)-enhancing Bbb Crossingmentioning
confidence: 99%
“…Another recent study of ginsenoside Rg3 and thioflavin T delivery reported that angiopep-2-conjugated PLGA NPs allowed the encapsulated compounds to cross the BBB and reach glial cells, exhibiting neuroprotective effects based on its antioxidant, anti-inflammatory, antiapoptotic, and anti-Aβ plaque activities in an in vitro BBB model [ 174 ]. The angiopep-2 ligand can specifically bind to low-density lipoprotein receptor-related protein-1 (LRP-1) on the surface of the brain capillary endothelial cells, thereby facilitating cellular uptake across the BBB via receptor-mediated endocytosis [ 174 , 175 ].…”
Section: Various Nanocarriers Containing Natural Compounds For Thementioning
confidence: 99%
“…Thus, the BBB is a physiologic barrier that limits the passage of most molecules in order to protect the stability of the brain. 13,14 Similarly, the BBB limits the entry into the brain of many contrast agents that could improve the diagnosis and evaluation of brain diseases, including brain tumors.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] The angiopep family of peptides can also cross the BBB via a low-density lipoprotein receptor-related protein (LRP) mediated pathway. 13,25 Among them, angiopep-2 with a molecular weight of 2.4 kDa promotes receptor-mediated transport through LRP1, resulting in higher in vivo and in vitro transcytosis capacity than other targeting ligands. 26,27 Angiopep-2 can also target gliomas due to the high expression of LPR1 on the surface of glioma cells.…”
Section: Introductionmentioning
confidence: 99%